2019
DOI: 10.31680/gaunjss.513784
|View full text |Cite
|
Sign up to set email alerts
|

Sporda Yetenek Seçimi ve Spora Yönlendirmede 9-10 Yaş Çocukların Bazı Fiziksel Özellikleri ve Performans Profillerinin İncelenmesi: Kırıkkale Örneği

Abstract: Bu araştırmada 9-10 yaş grubu çocukların fiziksel özellikleri ve bazı performans profilleri incelenerek yetenek değerlendirmesinin yapılması, yetenek ve sporcu seçiminde antrenör ve beden eğitimi öğretmenlerinin bu konuda yapılacak olan çalışmalarına katkıda bulunması amaçlanmaktadır. Araştırmanın örneklemini Kırıkkale Merkez Şehit Ramazan Akçadağ İlköğretim Okulunda öğrenim gören (n=12 erkek) ve (n=18 kız) oluşturmaktadır. Katılımcı çocuklara fiziksel ve performans verilerini tanımlamada eurofit test bataryas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…These investments do not only cover the training of athletes but also include finding and selecting the staff who will manage the sport, training and increasing their performance. In terms of sports practice, it has been reported that talent training is as important as talent selection for superior success (Güçlüöver et al, 2019, Karaca et al,2021. There is a continuous improvement in performance values and efforts to unearth talented athletes and good referees who can manage sports competitions.…”
Section: Introductionmentioning
confidence: 99%
“…These investments do not only cover the training of athletes but also include finding and selecting the staff who will manage the sport, training and increasing their performance. In terms of sports practice, it has been reported that talent training is as important as talent selection for superior success (Güçlüöver et al, 2019, Karaca et al,2021. There is a continuous improvement in performance values and efforts to unearth talented athletes and good referees who can manage sports competitions.…”
Section: Introductionmentioning
confidence: 99%